Skeletal Muscle Fiber Type in Hypoxia: Adaptation to High-Altitude Exposure and Under Conditions of Pathological Hypoxia - Chaillou, Thomas (Frontiers in Physiology, 2018)
Skeletal muscle is able to modify its size, and its metabolic/contractile properties in response to a variety of stimuli, such as mechanical stress, neuronal activity, metabolic and hormonal influences, and environmental factors. A reduced oxygen availability, called hypoxia, has been proposed to induce metabolic adaptations and loss of mass in skeletal muscle. In addition, several evidences indicate that muscle fiber-type composition could be affected by hypoxia. The main purpose of this review is to explore the adaptation of skeletal muscle fiber-type composition to exposure to high altitude (ambient hypoxia) and under conditions of pathological hypoxia, including chronic obstructive pulmonary disease (COPD), chronic heart failure (CHF) and obstructive sleep apnea syndrome (OSAS). The muscle fiber-type composition of both adult animals and humans is not markedly altered during chronic exposure to high altitude. However, the fast-to-slow fiber-type transition observed in hind limb muscles during post-natal development is impaired in growing rats exposed to severe altitude. A slow-to-fast transition in fiber type is commonly found in lower limb muscles from patients with COPD and CHF, whereas a transition toward a slower fiber-type profile is often found in the diaphragm muscle in these two pathologies. A slow-to-fast transformation in fiber type is generally observed in the upper airway muscles in rodent models of OSAS. The factors potentially responsible for the adaptation of fiber type under these hypoxic conditions are also discussed in this review. The impaired locomotor activity most likely explains the changes in fiber type composition in growing rats exposed to severe altitude. Furthermore, chronic inactivity and muscle deconditioning could result in the slow-to-fast fiber-type conversion in lower limb muscles during COPD and CHF, while the factors responsible for the adaptation of muscle fiber type during OSAS remain hypothetical. Finally, the role played by cellular hypoxia, hypoxia-inducible factor-1 alpha (HIF-1α), and other molecular regulators in the adaptation of muscle fiber-type composition is described in response to high altitude exposure and conditions of pathological hypoxia.